SUFISM, SPIRITUAL PERFORMATIVITY AND THEOLOGICAL CONTESTATIONS: PARALLELISMS OF THE ACEH AND PERAK SULTANATES ACROSS THE CENTURIES - Raja Halid, Raja Iskandar (International journal of Asia-Pacific studies, 2022)
Since the thirteenth century, longstanding connections between tariqa (Sufi Orders) and Malay Sultanates brought new Islamic knowledge and practices which were fused with local traditions. The coming of Islam also brought the nobat musical ensemble and religious-related musical practices. From the court of Pasai, North Sumatera, the ensemble later spread to other parts of the Malay world and was still played in the succeeding Aceh sultanate in the early seventeenth century. Evidence for this exists in the court manual, Adat Aceh, which details the use of music in royal religious processions and the practice zikir by the Sultan and his subjects. The Sufi spiritual performativity continued in the 1980s at the court of Perak with the introduction of the Naqshbandi Haqqani tariqa, where certain devotional-musical practices such as zikir, qasida, and mawlid were occasionally performed. However, the nobat was not used in these Sufi practices but replaced by percussion-based musical ensembles. Both these Naqshbandi Sufi tariqa were theologically contested, and their esoteric doctrines were considered blasphemous by those with religious power. This article examines the parallel existence of two Malay sultanates in different times, their connections to branches of Sufi tariqa, musical practices and the contestations that ensued.